The impact of online health community engagement on lifestyle changes: A serially mediated model - Zhou, Ping; Zhao, Yujie; Xiao, Suping; Zhao, Kangsheng (Frontiers in Public Health, 2022)
Background Due to reduced physical labor and increased food availability, making healthy lifestyle changes is becoming increasingly challenging. Prior studies have suggested that strong ties (such as friends or family members) help promote positive lifestyle behavior changes while weak ties like online friends hardly make a difference in activating healthy lifestyle changes. More recent studies have found evidence of positive lifestyle changes brought about by health APPs. Yet, the process through which online health community (OHC) engagement is related to healthy lifestyle changes has not been fully explored. Methods Drawing on social network theory and the self-efficacy literature, we argued that the information and emotional support which users obtained from OHCs is positively associated with health self-efficacy, which in turn is positively associated with lifestyle changes. Then we constructed a serially mediated model between OHC engagement and healthy lifestyle changes and collected 320 valid questionnaires through an online survey. We tested the model by applying structural equation modeling via Mplus 8.3, which uses bootstrapping (5,000 samples) to test the significance of the mediated paths. Results This study demonstrated that the informational and emotional support that users receive from OHC engagement positively affects healthy lifestyle changes via the mediating role of health self-efficacy. We also found that healthy lifestyle changes are an outcome of enhanced health self-efficacy through the effect of informational and emotional support from OHC engagement. Conclusions Our findings help explain how OHC users make healthy lifestyle changes by utilizing the informational and emotional support to develop health self-efficacy. The results also highlight the value of informational and emotional support as important resources which users acquire from OHC engagement. Thus, we suggest that OHC users utilize the informational and emotional support to enhance health self-efficacy and facilitate healthy lifestyle changes. Future research could explore the dynamic process through which OHC engagement influences lifestyle changes by designing longitudinal research and addressing the limitations of the present study.